2014
DOI: 10.1089/cap.2013.0066
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Parent Distress Following Pediatric Burns and Identification of Risk Factors for Young Child and Parent Posttraumatic Stress Disorder

Abstract: The findings from this study suggest that parents' responses to a traumatic event may play a particularly important role in a young child's psychological recovery. However, further research is needed to confirm the direction of the relationship between child and parent distress. This study identified variables that could be incorporated into screening tools or targeted by early intervention protocols to prevent the development of persistent child and parent PTSS following medical trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 34 publications
4
83
2
Order By: Relevance
“…Parental post-traumatic stress symptoms are reported to be a common consequence in the aftermath of a burn event [18,19]. The scars which are directly linked to the burn event may act as a reminder and therefore may play a role in parental observations [20].…”
Section: Introductionmentioning
confidence: 99%
“…Parental post-traumatic stress symptoms are reported to be a common consequence in the aftermath of a burn event [18,19]. The scars which are directly linked to the burn event may act as a reminder and therefore may play a role in parental observations [20].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary research into the resilience of pediatric burn survivors and resilience in their caregivers concluded that they were correlated, with a child's positive adjustment and well-being post-burn being affected by the psychological responses of the caregiver [146]. This again ties in with the knowledge that parent stress reactions can affect the child's own reactions to a burn or traumatic injury [23,98,99].…”
Section: Discussionmentioning
confidence: 94%
“…Parents and caregivers have been demonstrated to use negative coping reactions such as blame when caring for a burn-injured child and experience feelings of guilt [22]. Accordingly, research has also shown that a child's psychosocial recovery can be impacted on by parents' responses to the burn event [23]. There is evidence that parent distress levels are not influenced by the size of the burn [24], however the research focus still lies primarily with children who sustain major burn injuries.…”
Section: Experiencementioning
confidence: 99%
See 2 more Smart Citations